2020
DOI: 10.4103/jehp.jehp_86_20
|View full text |Cite
|
Sign up to set email alerts
|

Parental influences on medical students' self-efficacy and career exploration in collectivist culture

Abstract: INTRODUCTION: Families, especially parents, play an important role in identifying their children's talents and directing their educational journey. The role of parents in their children career applies both to collectivist and to noncollectivist culture. AIM: To examine the correlation between parental influences on medical students' self-efficacy and career exploration in collectivist culture. METHODS: This research was a quantitative study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Psychology Research and Behavior Management 2021:14 558 perceive that their parents strongly expect them to gain a prestigious career in line with Asian cultural values, which contributes to negative long-term effects. 63,64 Moreover, the strict isolation in Chongqing, China led to a lack of entertainment and irregular daily routines, and medical students expressed an urgent desire to return to normal school life and tended to pay special attention to the control of the coronavirus, which showed a positive association with PS, in line with a study of nursing students in Turkey. 47 Comparing the pre-epidemic literature, the results of this study suggested that the COVID-19 crisis did affect the distribution of stressors among medical students.…”
Section: Dovepressmentioning
confidence: 85%
“…Psychology Research and Behavior Management 2021:14 558 perceive that their parents strongly expect them to gain a prestigious career in line with Asian cultural values, which contributes to negative long-term effects. 63,64 Moreover, the strict isolation in Chongqing, China led to a lack of entertainment and irregular daily routines, and medical students expressed an urgent desire to return to normal school life and tended to pay special attention to the control of the coronavirus, which showed a positive association with PS, in line with a study of nursing students in Turkey. 47 Comparing the pre-epidemic literature, the results of this study suggested that the COVID-19 crisis did affect the distribution of stressors among medical students.…”
Section: Dovepressmentioning
confidence: 85%
“…This may also create further difficulty in the conceptualization and operationalization of the construct (Attanasio et al, 2019). Another possible explanation is that parental expectationsalong with other attributes of parental cognitions such as parental values, beliefs, and attitudesare considered as significant source of youth's self-efficacy and career exploration in the collectivist environment (e.g., Jasmon et al, 2020;Sawitri & Creed, 2017). This may also explain why the four studies examining the influence of parental cognitions included in the meta-analysis were all conducted in a collectivist cultural context (i.e., Indonesia) and contributed the largest effect size within this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%